2017
DOI: 10.21608/jfds.2017.37112
|View full text |Cite
|
Sign up to set email alerts
|

Production of Natural Pigments from Monascus ruber by Solid State Fermentation of Broken Rice and its Application as Colorants of Some Dairy Products

Abstract: The present study was aimed to maximize the production of natural pigments from Monascus ruber Went AUMC 5705 by solid state fermentation of broken rice to be a safe and healthy substitute of the harmful chemical dyes in the coloring of some flavored dairy products. Maximum pigments productivity was achieved under the following conditions: initial substrate moisture content 39%, substrate particle size 2-2.5 mm, PH 6.5, inoculums size 126×104 spores per 10 g dried rice and incubation period of 15 days at 30°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These results are in agreement with previous investigators who reported that food products gain more intense and stable color and improved organoleptic characteristics when M. purpureus pigments were used (Hamano and Kilikian, 2006 and Mal'a et al, 2010 ; Gomah et al, 2017 ; Abdel-Raheam et al, 2019 , 2021 ; Darwesh et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with previous investigators who reported that food products gain more intense and stable color and improved organoleptic characteristics when M. purpureus pigments were used (Hamano and Kilikian, 2006 and Mal'a et al, 2010 ; Gomah et al, 2017 ; Abdel-Raheam et al, 2019 , 2021 ; Darwesh et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, it can be used for poultry products such as poultry salami (Mal'a et al, 2010 ) and for sweet products such as lollipops, jelly beans (Darwesh et al, 2020 ), and drops sweets (Abdel-Raheam et al, 2021 ). The results by previous investigators reported that food products gain more intense and stable color and improved organoleptic characteristics when M. purpureus pigments were used (Hamano and Kilikian, 2006 and Mal'a et al, 2010 ; Gomah et al, 2017 ; Abdel-Raheam et al, 2019 , 2021 ; Darwesh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The addition of natural pigments to food has several advantages, with the main purpose of stimulating and improving sensory perception, in addition to reducing the use of synthetic components, due to health and safety concerns (Egea and Marcionilio, 2022). In this sense, due to its production capacity, the Monascus pigment is often evaluated for its application in food and beverages, including dairy products, candies, bakery products, cereals, meat products, and beverages, among others (Table 1) (Mal'a et al, 2010;Gomah et al, 2017;Darwesh et al, 2020;Monteiro et al, 2021;Abdel-Raheam et al, 2022;Srianta et al, 2022).…”
Section: Monascus Sp and Its Pigment Production Potentialmentioning
confidence: 99%
“…In addition, it was verified that the addition of pigment confers the presence of bioactive substances, mainly phenolic compounds, with special antioxidant and antimicrobial activities. In all the cases cited, the added pigment seemed to withstand the process conditions, not being degraded to the point of making its application unfeasible, much less influencing the attractiveness and acceptance by the consumers (Mal'a et al, 2010;Gomah et al, 2017;Darwesh et al, 2020;Monteiro et al, 2021;Abdel-Raheam et al, 2022;Srianta et al, 2022).…”
Section: Monascus Sp and Its Pigment Production Potentialmentioning
confidence: 99%